Day case surgery guidelines. Issue 2 (February 2017) - Anderson, Tom; Walls, Martin; Canelo, Ruben
Abstract: Day surgery is a continually developing and expanding specialty throughout the world. Technical improvements within surgery and anaesthesia allow increasingly complex procedures to be performed as day case surgery, with advantages to hospital and patient. The NHS Modernisation Agency recommends 75% of all surgical procedures performed in a Trust be as day case procedures. Day case surgery guidelines exist to assist and encourage departments in running an effective service. Day surgical units must select appropriate cases based on patient, surgical and social factors, via a preoperative assessment service usually run by specialist nurses, consultant surgeons and anaesthetists. Stable medical conditions such as hypertension and diabetes mellitus do not preclude day case surgery. Patients are assessed individually. The obese patient must be carefully screened before being listed for day case surgery. Both general and regional anaesthesia have been shown to be safe and effective in day surgery patients. Achieving good analgesia and antiemesis is vital in ensuring patients are discharged on the day of surgery. Nurse-led discharge based on local departmental protocol is common practice. Both patient and GP must be issued postoperative instructions. Future expansion is likely to see selected emergency and semi-elective surgical patients managed as day case procedures.